2010
DOI: 10.1007/s00198-010-1501-1
|View full text |Cite
|
Sign up to set email alerts
|

Markers of bone turnover for the prediction of fracture risk and monitoring of osteoporosis treatment: a need for international reference standards

Abstract: BTM hold promise in fracture risk prediction and for monitoring treatment. Uncertainties over their clinical use can be in part resolved by adopting international reference standards.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
837
4
65

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 972 publications
(923 citation statements)
references
References 158 publications
(159 reference statements)
17
837
4
65
Order By: Relevance
“…The LSC was less for the raloxifene study -45% CTX and -27% PINP in comparison to the TRIO study (-56% CTX, -38% PINP). There are several ways that LSC can be calculated [10,29] .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The LSC was less for the raloxifene study -45% CTX and -27% PINP in comparison to the TRIO study (-56% CTX, -38% PINP). There are several ways that LSC can be calculated [10,29] .…”
Section: Discussionmentioning
confidence: 99%
“…In clinical trials, the changes in bone turnover markers have been shown to be related to change in fracture risk [10] . There is evidence that there is an association between the change in bone formation markers but not bone resorption markers on raloxifene and the reduction in spine fracture risk [5,[11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations